Decision-making under information overload : visual representation and ‘fast and frugal’ heuristics as strategies for dealing with information overload - Sephton, Katherine Alison (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.